SYSTEM OF MACHINERY FOR COMPLEX MECHANIZATION FOR RECLAMATION WORK - V. S. Puninskiy (Сельскохозяйственные машины и технологии)
Meliorative fleet replacement and expansion of lands areas of melioration systems during radical improvement of not used, degraded layland are the two interconnected directions. They can be provided during introduction of science based modern System of technologies and machines for the complex mechanization of meliorative works. This System is the most fully answering to a problem of import substitution of the food, carrying out monitoring of the market of digging and special meliorative equipment. The authors presented the review of realization of System of machinery during the period since 1955 so far. Machines test play a part in regulation of the meliorative equipment market. Improvement of basic technologies of performance of maintenance activities on melioration systems, along with addition with new operations, is possible by creation of the multipurpose combined machines with working tools which novelty is confirmed with patents. The authors proved the project of part of System of machinery for maintenance activities on melioration systems for the period 2015-2020.